Mitochondrial-Dependent and Independent Functions of PINK1 - Chen, Xiusheng; Wang, Qi; Li, Shihua; Li, Xiao-Jiang; Yang, Weili (Frontiers in Cell and Developmental Biology, 2022)
PINK1 has been characterized as a mitochondrial kinase that can target to damaged mitochondria to initiate mitophagy, a process to remove unhealthy mitochondria for protecting neuronal cells. Mutations of the human PINK1 gene are also found to cause early onset Parkinson disease, a neurodegenerative disorder with the pathological feature of mitochondrial dysfunction. Despite compelling evidence from in vitro studies to support the role of PINK1 in regulation of mitochondrial function, there is still lack of strong in vivo evidence to validate PINK1-mediated mitophagy in the brain. In addition, growing evidence indicates that PINK1 also executes function independent of mitochondria. In this review, we discuss the mitochondrial dependent and independent functions of PINK1, aiming at elucidating how PINK1 functions differentially under different circumstances.